2011
DOI: 10.17221/246/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance of Enterococcus species isolated from raw foods of animal origin in South West part of Slovakia

Abstract: Kročko M., Čanigová M., Ducková V., Artimová A., Bezeková J., Poston J. (2011): Antibiotic resistance of Enterococcus species isolated from raw foods of animal origin in South West part of Slovakia. Czech J. Food Sci., 29: 654-659.We determined the prevalence and antibiotic resistance of enterococci isolated from raw foods of animal origin. All samples were positive for enterococci. The lowest count of enterococci was found in pork (2.00 log CFU/cm 2 ), while bryndza cheese contained the highest count (4.99 lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
3
21
1
Order By: Relevance
“…Other studies have shown that E. faecalis and E. faecium constitute the dominant flora in isolates obtained from animal‐originated foods (Cho et al, 2013; Jiménez et al, 2013; Morandi et al, 2015; Valenzuela, Benomar, Abriouel, Cañamero, & Gálvez, 2010; Yogurtcu & Tuncer, 2013). In contrast to our results, vancomycin‐resistant E. faecalis and/or E. faecium strains were isolated from animal‐originated foods in Slovakia (Kročko et al, 2011), Korea (Cho et al, 2013), Turkey (Çetinkaya et al, 2013), Spain (Guerrero‐Ramos et al, 2016), and Nigeria (Igbinosa & Beshiru, 2019). Pediococcus and Weissella can be isolated from animal‐originated foods as well as the commonly‐isolated Enterococcus species.…”
Section: Resultscontrasting
confidence: 99%
“…Other studies have shown that E. faecalis and E. faecium constitute the dominant flora in isolates obtained from animal‐originated foods (Cho et al, 2013; Jiménez et al, 2013; Morandi et al, 2015; Valenzuela, Benomar, Abriouel, Cañamero, & Gálvez, 2010; Yogurtcu & Tuncer, 2013). In contrast to our results, vancomycin‐resistant E. faecalis and/or E. faecium strains were isolated from animal‐originated foods in Slovakia (Kročko et al, 2011), Korea (Cho et al, 2013), Turkey (Çetinkaya et al, 2013), Spain (Guerrero‐Ramos et al, 2016), and Nigeria (Igbinosa & Beshiru, 2019). Pediococcus and Weissella can be isolated from animal‐originated foods as well as the commonly‐isolated Enterococcus species.…”
Section: Resultscontrasting
confidence: 99%
“…Resistance to rifampin seems to be widely spread among Enterococci and was the highest percentage between the tested antimicrobials (85.3%). This was similar to the results of Sarra et al [36], while, Kročko et al [30] reported that tetracycline and gentamicin resistance was the most common. Sarra et al [36] found that, none of the tested isolates demonstrated resistance to ampicillin, vancomycin and gentamicin.…”
Section: Discussionsupporting
confidence: 90%
“…Notably, E. faecalis was the predominant species recovered (42.8%), followed by E. faecium (39.2%), E. casseliflavus (3.5%) and only 4 isolates were not identified to species level (14.2%). Similar results of E. faecalis predominance but with higher percentage (49%) were reported [30]. In addition, Gangurde et al [31] in South West part of Slovakia isolated E. faecalis (60%) in followed by E. faecium 32.2%.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations